Rancangan Sumur Resapan Air Hujan sebagai Upaya Pengurangan Limpasan di Kampung Babakan, Cibinong, Kabupaten Bogor - Lussiany Bahunta; Roh Santoso Budi Waspodo (Jurnal Teknik Sipil dan Lingkungan, 2019)
Land use change due to housing construction can indirectly damage the water catchment area. This resulted in a decrease in the area of rainwater absorption that caused rain water collected on existing drainage channels. This study aims to analyse the number and dimensions of infiltration wells in reducing the volume of inundation and determine the value of effectiveness reduction of runoff. The infiltration wells was used to collect rainwater and absorb it into the soil. Based on the calculation in Babakan Village area of 2.42 ha, with runoff coefficient of 0.4 for village character, and design rainfall of 97.36 mm/day, the estimated flood volume based on SNI 03-2453-2002 was 805790.30 liter or 805.79 m3. Based on the calculation, Babakan Village needed 115 infiltration wells and 76 trenches. With the infiltration wells and trenches, the total flood volume can be reduced 620.62 m3 or 77.02% of the total runoff.Keywords: design rainfall, infiltration wells, runoff, trenches